Ensaios de piezocone em um depósito de argila mole da cidade do Recife - Oliveira, Joaquim Teodoro Romão de (1991)
Piezocone tests been been performed in a soft clay deposit at Recife using the equipment developed at COPPE/UFRJ. Laboratory tests have also been performed. Piezocone test results have been compared with laboratory test results, as well as with data from other deposits. The comparison between piezocone and laboratory tests have shown a good agreement for many soil parameters.